Clinical burden of propionic acidemia in the United States: a claims-based study by age stratum - Geetanjoli Banerjee; Sue Perera; Fan Mu; Erin Cook; Mu Cheng; Adina Zhang; Jessie Jie Lan; Lin Zou; Vanja Sikirica (Orphanet Journal of Rare Diseases)
Abstract Background Patients with propionic acidemia (PA) may face recurrent metabolic decompensation events (MDEs) and multisystemic complications. This study compared characteristics and clinical outcomes of patients with PA and matched non-PA controls by age stratum. Methods Patients with PA from the US IQVIA PharMetrics Plus claims database (10/2015‒6/2022) had their follow-up time partitioned into age strata (0‒2, 3‒6, 7‒12, 13‒17, ≥ 18 years) and were matched 1:1 to randomly selected non-PA controls within each stratum. MDEs were identified as hospitalizations with claims for hyperammonemia and/or metabolic acidosis. Hospitalizations with claims for PA signs and symptoms were evaluated. Results Among 191 patients with PA and 230 matched non-PA controls (median follow-up: 2.7 years), patients with PA had more comorbidities (neurologic/nervous system, cytopenias, growth, metabolism, cardiac system; listed in order of frequency) across all age strata. The overall MDE rate for patients with PA was 0.5 per patient-year (PPY) while hospitalizations with various PA signs and symptoms ranged from 0.3 to 0.6 PPY. MDE rates were highest in those aged 3‒6 years (1.4 PPY), lowest in the 13‒17 years stratum (0.1 PPY), and rose again in adults (0.2 PPY). Patients with MDEs (31.4%) had a significantly higher burden of PA-related symptoms and comorbidities than those without; both groups showed even greater differences when compared to controls. Conclusions Patients with PA across all age strata, with and without MDEs, experience a substantial burden of disease-related comorbidities, complications, and healthcare visits compared with matched non-PA controls, which highlights the need for improved clinical outcomes in these patients.